QoE Enhancement using SVC and Throughput Prediction - Nos, Tarnim (2025)
A Master of Science thesis in Electrical Engineering by Tarnim Nos entitled, “QoE Enhancement using SVC and Throughput Prediction”, submitted in September 2025. Thesis advisor is Dr. Mahmoud H. Ismail Ibrahim and thesis co-advisors are Dr. Mohamed Hassan and Dr. Taha Landolsi. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).